PREVENTIVE TRAINING PROGRAM TO REDUCE COMMON KNEE JOINT INJURIES AMONG WRESTLERS - Jafar Habib Zaher; Hamdi Chtourou (American Journals, 2023)
This research aims to reduce knee joint injuries among wrestlers by identifying the most common knee injuries, designing a preventive training program, and assessing the impact of the preventive training program on knee joint injuries among wrestlers. The researcher employed an experimental approach due to its suitability for the nature of the research, using a single-group experimental design. The research sample was purposively selected and consisted of young wrestlers from the researcher's club, belonging to the youth category and registered with the Tunisian Wrestling Federation. The total population of the research sample was 16 wrestlers, divided into 10 wrestlers in the survey sample and 6 wrestlers in the core sample, aged between 14 and 16 years old. The proposed preventive training program was applied, and data were collected through measurements, statistically processed, and important results were obtained. The program had a positive impact on improving the neural conduction velocity of both the right and left arms. Additionally, it led to improvements in muscle strength and range of motion. One of the key recommendations is to generalize the derived preventive program to coaches, load regulators, and injury specialists, utilizing the program's exercises to reduce the physical susceptibility to injuries among athletes.
Keywords: Training program, sports injuries, knee joint, wrestling.